Analysis and forecast of the dynamics of passenger transportation by public land transport - Butkevičius, Jonas; Mazūra, Mindaugas; Ivankovas, Valdas; Mazūra, Skirmantas (Transport, 2004)
In the presented paper the dynamics of passenger haulage by public transport is considered and a forecast is made. In Lithuania the total volume of passenger transportation by public land transport considerably decreased in the period from 1992 to 2001. In fact, the number of passengers carried by these transport facilities decreased by 3.1 times. The most considerable decrease was found on the local (suburban) bus routes and on international railway routes – by 5.6 and by 5 times, respectively. Long‐distance transportation by bus which decreased only by 1.6 times was the least affected. The paper aims to identify major causes of transportation decrease common to road and railway transport (i.e. considerable growth of tariffs, fast growth of the number of personal motor cars, wear of transport facilities, lack of comfort, low prestige of public transport, etc.). The emphasis is placed on making a forecast of passenger traffic by using a multiple regression. The calculations show that the national income is the most reliable parameter for making forecasts of land transport development compared to a number of others, including national income, a gross national product, average monthly payment, household income and expenditures, national wealth, the index of production and users’ cost, and the variation of consumer goods and services. The forecasts show that passenger haulage by public transport will reach 575 m by 2010, while by 2015 it will grow up to 893 m. This means that transportation will increase by 1,6 times and 2,3 times, respectively, compared to passenger haulage in 2001. However, passenger transportation in 2015 will not achieve the volume found in 2001. The data of the considered forecast were used developing the strategies of national road and railway transport development.First Published Online: 27 Oct 2010